MODERN APPROACHES TO THE TREATMENT OF TYPE 2 DIABETES MELLITUS WITH CHRONIC HEART FAILURE - khatov Sh.Sh., Najmutdinova D.K., (Central Asian Journal of Medicine, 2025)
Type 2 diabetes mellitus (DM2) and chronic heart failure (CHF) often occur together, exacerbating each other's course and worsening the patient's prognosis. The relationship between these diseases is determined by pathophysiological mechanisms, including insulin resistance, inflammation, and endothelial dysfunction. Diabetes mellitus, a widespread socially significant disease with numerous micro- and macrovascular complications, acts both as a risk factor for heart failure and as a condition that significantly exacerbates its course. The relationship between diabetes and CHF is complex and is caused by several mechanisms. Diabetes contributes to the development of cardiomyopathy, impaired diastolic function of the heart and the progression of coronary artery atherosclerosis, which eventually leads to the development or worsening of CHF [9].